Social Development of Early Children in Online Learning in the Time of the Covid-19 Pandemic (Universitas Negeri Semarang, 2022)
In order to stop the spread of Covid-19, all educational institutions conduct online learning, one of which is SALAM. Changes in the system affect the social development of children. Based on these problems, the objectives of this study are: (1) Analyzing Children's Social Development During the Application of Online Learning. (2) Factors influencing children's social development. (3) Finding the positive and negative impacts of online learning in the perspective of children's social development. This study uses a qualitative method with the type of case study research, the research subjects are the founders of SALAM, facilitators and parents of SALAM family planning, the data collection techniques are observation, interviews and documentation. Then the data analysis technique uses data reduction, data presentation, and drawing conclusions. In addition, the last step taken by the researcher was checking the validity of the data by using the data triangulation technique. The results of this study indicate that: (1). The social development experienced by Salam family planning children is very varied, indicated by the ability to play with peers, be tolerant, be cooperative, share, behave politely, respect the rights and opinions of others, and respond. (2) the factors that influence the social development of children consist of the family environment, maturity, economic status, education, and mental capacity. (3) The impact of online learning includes better social development at home, lots of new vocabulary, getting used to doing PHBS, lots of new creativity, being more responsible with themselves, being more emotional, seeking attention, children being less social with peers. Keywords: Online Learning, Social Development, Covid-19 Pandemic